4(x-1)+2x=6(x-6)

Simple and best practice solution for 4(x-1)+2x=6(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-1)+2x=6(x-6) equation:


Simplifying
4(x + -1) + 2x = 6(x + -6)

Reorder the terms:
4(-1 + x) + 2x = 6(x + -6)
(-1 * 4 + x * 4) + 2x = 6(x + -6)
(-4 + 4x) + 2x = 6(x + -6)

Combine like terms: 4x + 2x = 6x
-4 + 6x = 6(x + -6)

Reorder the terms:
-4 + 6x = 6(-6 + x)
-4 + 6x = (-6 * 6 + x * 6)
-4 + 6x = (-36 + 6x)

Add '-6x' to each side of the equation.
-4 + 6x + -6x = -36 + 6x + -6x

Combine like terms: 6x + -6x = 0
-4 + 0 = -36 + 6x + -6x
-4 = -36 + 6x + -6x

Combine like terms: 6x + -6x = 0
-4 = -36 + 0
-4 = -36

Solving
-4 = -36

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4s+7t=79 | | -8g=-9g+3 | | p=-5+2p | | 2(5)+3(0)= | | 6x+2x+x+3=39 | | -f=9f+10 | | x^2+2x+y^2+14y-5=0 | | -3(2h-8)=-32-7h | | 6x+10=-3x+109 | | 1-6d=-5d | | 4k=-6 | | 3s+2t=30 | | 4b+6=7b | | -2k+9=-k | | 10x+4=-34 | | x+5=5x+6 | | 4(9-6)+4=2a-6 | | -0.4x+0.5x-9=5 | | -3f=-4f+9 | | 7x+5=-x+5 | | 3n-7(n+3)=7 | | 2[4+x]=-16 | | (4)-(-1)= | | 6u=5u-6 | | -89.0602=10.861b | | 16=8m | | 20x^3+24x^2+4x=0 | | -104=10-6w | | 3(7m+5)+4(3m-8)=148 | | 4(2+5-24)=52-13 | | -6f-5+7f=21 | | 2y+5x-1=2x+4x-2 |

Equations solver categories